2020
DOI: 10.3390/w12020331
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Induced Changes of Dissolved Organic Matter in a Humic-Rich and Forested Stream

Abstract: Photochemical processing is an important way to transform terrestrial dissolved organic matter (DOM) but was rarely investigated by ultra-high resolution mass spectrometry. We performed an irradiation experiment with water from a shaded forest stream flowing into a lit reservoir. Bacterial activity explained only 1% of dissolved organic carbon (DOC) decline in a combined bacterial and photodegradation approach. Photodegradation decreased the DOC concentration by 30%, the specific ultraviolet (UV) absorption by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 79 publications
6
43
0
Order By: Relevance
“…The lower HIX values in the raised WT treatment, regardless of flooding history, suggest less accumulation of the products of peat mineralization. Lower HIX is consistent with the increased Sr (Chen et al, 2011) observed at the raised WT treatment, and could also be reflecting increased photodegradation of the DOM as opposed to biological degradation of the DOM (Helms et al, 2008;Wilske et al, 2020). Increased photodegradation would be facilitated by the water table being at or slightly above the peat surface in the raised WT treatment.…”
Section: Insights Gained From Dom Compositionsupporting
confidence: 64%
“…The lower HIX values in the raised WT treatment, regardless of flooding history, suggest less accumulation of the products of peat mineralization. Lower HIX is consistent with the increased Sr (Chen et al, 2011) observed at the raised WT treatment, and could also be reflecting increased photodegradation of the DOM as opposed to biological degradation of the DOM (Helms et al, 2008;Wilske et al, 2020). Increased photodegradation would be facilitated by the water table being at or slightly above the peat surface in the raised WT treatment.…”
Section: Insights Gained From Dom Compositionsupporting
confidence: 64%
“…This might explain increasing numbers of lignin-like molecules along flow paths. In surface water, photodegradation possibly attenuates photosensitive TrOCs like gabapentin 17 or diclofenac 16 and DOM compounds 38 . During our sampling campaign, gabapentin and diclofenac did not decrease in surface water.…”
Section: Discussionmentioning
confidence: 99%
“…Dissolved organic matter (DOM) is the largest pool of organic matter in the sea and it plays an important role in carbon biogeochemical cycles of aquatic environments. DOM is composed of a series of organic compounds resulting from the release of bacteria, phytoplankton and macrophytes and their continuous transformation through photochemical and microbial processes [ 5 ]. Chromophoric dissolved organic matter (CDOM) is the primary DOM in aquatic environments, and it is one of the major determinants of optical descriptors of natural waters and can affect the availability and spectral quality of DOM in the water [ 6 ].…”
Section: Introductionmentioning
confidence: 99%